2014
DOI: 10.1007/s13187-014-0729-4
|View full text |Cite
|
Sign up to set email alerts
|

Acceptability and Cultural Appropriateness of Self-Help Booklets for Relapse Prevention in Puerto Rico

Abstract: Cigarette smoking is associated with a range of cancers and is related to five of seven leading causes of death in Puerto Rico. Minimal self-help interventions have shown promising results in reaching participants and preventing relapse from smoking. Specifically, a collection of 8 self-help booklets has demonstrated efficacy (Brandon et al., 2000; 2004). Those booklets have been transcreated into Spanish, with efforts to make them culturally appropriate across a range of Hispanic cultures. We conducted a pilo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…This is meaningful given that 3 calls is the minimum number recommended by the Quitline for effective treatment 14 and aligns with prior work indicating that completing more Quitline calls is associated with better cessation outcomes. [26][27][28] Previous research also indicates Hispanic smokers value personal contact as a part of intervention delivery, [29][30][31] which may account for the increased treatment call engagement and subsequently higher abstinence rates for Spanish-preferring patients. Another potential explanation is that Spanish-preferring individuals may have had higher treatment engagement rates because they simply perceived few alternative treatment options.…”
Section: Discussionmentioning
confidence: 99%
“…This is meaningful given that 3 calls is the minimum number recommended by the Quitline for effective treatment 14 and aligns with prior work indicating that completing more Quitline calls is associated with better cessation outcomes. [26][27][28] Previous research also indicates Hispanic smokers value personal contact as a part of intervention delivery, [29][30][31] which may account for the increased treatment call engagement and subsequently higher abstinence rates for Spanish-preferring patients. Another potential explanation is that Spanish-preferring individuals may have had higher treatment engagement rates because they simply perceived few alternative treatment options.…”
Section: Discussionmentioning
confidence: 99%
“…27 Another study, this one from South Korea, stated that smoking is more common among married individuals than single persons. 28 A critical look at these published findings reveals that, in studies reporting on Western culture, a higher prevalence of smoking was observed among individuals who lived alone than it was among those were married. Thus, while smoking is more prevalent in married Asians (living in Asia) than it is in those who live alone, the opposite is true in the Western culture: Smoking is more prevalent in individuals who live alone than it is in those who are married and living with a spouse.…”
Section: Discussionmentioning
confidence: 99%